Healthcare-associated viral respiratory infections in paediatric intensive care unit settings: More than just a sneeze - Kelly Feldman; Wendi Gornick; Beth Huff; Jasjit Singh (Elsevier, 2022)
Summary: Healthcare-associated infections (HAIs) affect patient health. Patients with Paediatric Intensive Care Unit (PICU) acquired viral respiratory infections had longer use of respiratory support. We found it's uncommon in ICUs to have high risk HAIs. RSV, parainfluenza, and hMPV are the most common, and 1/3 of patients required escalation in respiratory support and/or escalation in antibiotics. All patients had underlying comorbidities. In our series there were two deaths within 2 weeks of infection.